PENGEMBANGAN PENGELOLAAN BERBASIS MASYARAKAT PADA WISATA UJONG KAREUNG DI GAMPONG SUAK INDRAPURI - Ika Kusumawati (Jurnal Marine Kreatif, 2018)
Tourism coastal area is one form of application of community-based and sustainable tourism development. Through the development of tourist villages are expected to occur equitable in accordance with the concept of sustainable tourism development. Community participation is important in the implementation of development. In reality there is often a neglect of community participation, so that the community is still the object of the implementation of management. The development of the tourism village is a planned change in which local participation is required holistically. This activity aims: Provides an overview of how the development and management of attractions based on local communities. The development of Suak Indrapuri Village, Aceh Barat Regency, Aceh Province into a tourist village has not fully involved community participation. The challenge in the process of developing the tourist gampong in Suak Indrapuri is the lack of cooperation between local government / related agencies and gampong devices in the whole process of tourism development. Whereas when referring to a clean and sustainable government governance approach the role of the government is expected to be a facilitator by providing greater role and benefits to the local community. Good coordination is able to develop the area. It is desirable that existing natural resources are sustainable without reducing and damaging their quality.